Control de la facturación en los puntos de emisión de la empresa CDTRAP S.A. en la ciudad de Guayaquil periodo 2022 (transporte de carga pesada). - Calahurano Pacheco, Gigi Katiusca (2023)
Electronic invoicing has become increasingly common worldwide due to its benefits in terms of efficiency and cost savings. The adoption of electronic invoicing has accelerated in the last decade, driven by the European Directive 2014/55/EU. In the United States, the Electronic Signatures in Global and National Commerce Act of 1999 promoted the use of electronic invoicing. In Ecuador, electronic invoicing became mandatory in 2016 and in 2022, new regulations were established that made it mandatory for most taxpayers. The study analyzes how CDTRAP S.A. adapted to the new electronic invoicing process, including changes in the process, systems, and tools used by the company. This case study allows us to understand the challenges and opportunities involved in implementing electronic invoicing in the context of a heavy cargo transport company in the city of Guayaquil. This study focuses on using a mixed-method approach to collect and analyze qualitative data. The goal is to obtain detailed and in-depth information on the company's invoicing processes and procedures, and to identify the causes of possible difficulties in invoicing control. Electronic invoicing has generated significant changes in the company's invoicing process, including the acquisition of a complete integrated system, hiring personnel, and implementing new administrative procedures and policies.